With Language in Mind. Issue 2 (3rd April 2021) - de Villiers, Jill
ABSTRACT: Does language have a role to play in conceptual development, and if so, what is that role? Understanding the contents of another person's mind parallels the development in early childhood of mental state language. Does the conceptual understanding get reflected in and drive the language development, or does the language allow the representation of propositional attitudes like belief? The paper reviews the evidence and sets up the terms of the debate, focusing on the syntax for mental states. It also asks whether syntax development could serve as a scaffold for other concepts that are described by propositions rather than labels. Finally, it reviews experimentation on the syntax of embedded clauses, where subtle phenomena are acquired for which it is impossible to imagine nonverbal counterparts: here, language is human thinking.